2008
DOI: 10.1128/aem.00833-08
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Analysis of Field-Grown Soybeans with Different Nodulation Phenotypes

Abstract: Microorganisms associated with the stems and roots of nonnodulated (Nod؊ soybeans, whereas the abundance of basidiomycetes was just the opposite. The phylogenetic analyses suggested that these basidiomycetous fungi might represent a root-associated group in the Auriculariales. Principal-component analysis of the ARISA results showed that there was no clear relationship between nodulation phenotype and bacterial community structure in the stem. In contrast, both the bacterial and fungal community structures in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…Thus, there is a possibility that nodulation phenotype and host nitrogen status may affect the structure of the microbial community in shoots, as observed earlier in roots (Ikeda et al, 2008a). However, the cultureindependent analysis of soybean stem-associated microbial communities failed because of serious interference by plant DNA in the PCR amplification (Ikeda et al, 2008a). To overcome this problem, a method was recently developed for enriching the bacterial cells collected from soybean stems .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is a possibility that nodulation phenotype and host nitrogen status may affect the structure of the microbial community in shoots, as observed earlier in roots (Ikeda et al, 2008a). However, the cultureindependent analysis of soybean stem-associated microbial communities failed because of serious interference by plant DNA in the PCR amplification (Ikeda et al, 2008a). To overcome this problem, a method was recently developed for enriching the bacterial cells collected from soybean stems .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, a method was recently developed for enriching the bacterial cells collected from soybean stems . The enrichment method allows the construction of a clone library of the bacterial 16S ribosomal RNA (rRNA) genes, which provides better resolution for examining the microbial community structures compared with the limited analyses in previous studies based mainly on fingerprinting methods (Offre et al, 2007;Ikeda et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that symbiosis-defective mutants of Medicago truncatula (30) and soybean (16,32) possess bacterial and fungal communities in their roots different from those in wild-type host plants and that certain bacteria preferentially associate with mycorrhizal roots (41). These findings indicate that genetic alteration in RN/AM signaling pathways can also alter the microflora of the rhizosphere.…”
mentioning
confidence: 88%
“…These findings indicate that genetic alteration in RN/AM signaling pathways can also alter the microflora of the rhizosphere. Interestingly, analyses of the rhizosphere of soybeans indicated that the bacterial community structures of nonnodulated soybeans were more similar to those of hypernodulated soybeans than to those of wild-type soybeans (16). Since nodulation is autoregulated by signal transduction between root and shoot tissues (31), it is of interest to compare bacterial communities in shoots between wild-type and symbiosis-defective mutants.…”
mentioning
confidence: 99%